DEVELOPMENT OF LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES ON PRODUCT BRANDING MATERIALS IN VOCATIONAL HIGH SCHOOLS - rangga dino Alfian; Fahmy Zuhda Bahtiar; Fathur Rahman; Nurul Burhan (Universitas Negeri Semarang, 2025)
The purpose of this study is to analyze the needs of teachers and students for learning media, to determine the feasibility of learning media, and to measure the effectiveness of this learning media on Shiva learning outcomes. This type of research is Research and Development (R&D). With the validation of the research instrument, it is then continued with the research procedure using 10 stages, and quantitative descriptive data analysis techniques. The results of the media feasibility test obtained a percentage of 95% for the media assessment so that the product was categorized as